The effect of breast milk nesfatin-1 and ghrelin levels on growth in infants with SGA - Filibeli, Berna Eroğlu; Bayraktar, Melike Karabulut; Aksun, Saliha; Çatlı, Gönül; Yıldırım, Jülide Gülizar; Dündar, Bumin Nuri (The Turkish Journal of Pediatrics, 2022)
Background. Current studies claim that peptides such as leptin, adiponectin, ghrelin, and nesfatin-1 found in breast milk may be responsible for the growth of infants. Therefore, we aimed to determine the association between breast milk total ghrelin and nesfatin-1 levels and anthropometric measurements of infants who were small for gestational age (SGA). Methods. 20 SGA and 20 appropriate for gestational age (AGA) infants were enrolled in the study. Anthropometric measurements of infants were carried out at birth, 1st, and 4th months. In addition, total ghrelin and nesfatin-1 levels in the breast milk were concomitantly measured. Results. Total ghrelin at the 4th month in breast milk waslower-level in the SGA group (p=0.015). In both groups, nesfatin-1 levels at the 4th month were lower than the values at the 1st month. Additionally, nesfatin-1 levels of SGA infants at the 4th month were higher (p=0.035). Conclusions. Breast milk total ghrelin and nesfatin-1 levels differed in both groups, and it is probably referred to the growth discrepancy of these infants during the first months of life. Furthermore, we consider that higher breast milk nesfatin-1 levels at the 4th month may be a preventive against obesity in SGA infants who have potential risk for obesity in childhood and adulthood.